2018
DOI: 10.1177/1071100718760845
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Evaluation of Circumtibial and Transmembranous Routes for Posterior Tibial Tendon Transfer for Dropfoot

Abstract: The CT transfer had the highest tendon gliding resistance, achieved less dorsiflexion and had a supination moment. Clinical Relevance We suggest that the transmembranous tibialis posterior tendon transfer should be the transfer of choice. The potential bowstringing effect when performing a tibialis posterior tendon transfer subcutaneously (TMAR) could be avoided if the transfer is routed under the retinaculum, without significant compromise of the final function and even with a possible better ankle range of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“… 13 The STS-T proposes a stronger reconstruction model that permits sharing pull force strength and soft-tissue balance, which allows an earlier joint motion and better muscle performance. 14 , 15 Some studies propose the use of a long-time lower-leg splint (or combined with a cast) up to 6-8 weeks after tendon transfer. 16 , 17 This delay in the rehabilitation process increases muscle weakness and arthrofibrosis risk because of prolonged immobilization.…”
Section: Discussionmentioning
confidence: 99%
“… 13 The STS-T proposes a stronger reconstruction model that permits sharing pull force strength and soft-tissue balance, which allows an earlier joint motion and better muscle performance. 14 , 15 Some studies propose the use of a long-time lower-leg splint (or combined with a cast) up to 6-8 weeks after tendon transfer. 16 , 17 This delay in the rehabilitation process increases muscle weakness and arthrofibrosis risk because of prolonged immobilization.…”
Section: Discussionmentioning
confidence: 99%
“…An a priori power analysis was calculated (G*Power 3.0.10) using previously reported means and standard deviations from a study on transmembranous PTT transfer. 18 An effect size of 1.2 was determined and used to estimate that a minimum of 7 specimens would be required for 80% power with alpha set at 0.05. We performed statistical analysis using PRISM software (version 7.04; Graphpad Software Inc, San Diego, CA).…”
Section: Methodsmentioning
confidence: 99%
“…There are no clinical data to favor one technique; however, placing the posterior tibial tendon beneath the retinaculum will avoid bowstringing of the tendon, and a cadaveric biomechanical study has indicated this will not adversely affect the function. 37…”
Section: Musculotendinous Perspectivementioning
confidence: 99%